The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1007/s00170-020-06199-5
|View full text |Cite|
|
Sign up to set email alerts
|

Geometry assessment of ultra-short pulsed laser drilled micro-holes

Abstract: Ultra-short pulsed laser ablation enables a defined generation of micro-holes. A parameter study on the ablation characteristics of copper clearly reveals a benefit for green wavelength with lower threshold fluence, simultaneously increasing the Rayleigh length. The use of a circular drilling method allows a defined manufacturing of micro boreholes and micro through-holes with 35 μm diameter of up to 165 μm and 300 μm length. Introducing high-resolution micro-computed X-ray tomography studying the micro-hole e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…In order to deal with the experimental data effectively, the results of the orthogonal experiments were processed and analyzed by the polar difference analysis method selected in this paper [25]. The mean value of the experimental investigation index (the entrance exit diameters and taper) of each factor at different levels was used as the measurement factor, and then the extreme difference value of these factors was calculated as the experimental investigation index of each factor at different levels.…”
Section: Data Processing Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to deal with the experimental data effectively, the results of the orthogonal experiments were processed and analyzed by the polar difference analysis method selected in this paper [25]. The mean value of the experimental investigation index (the entrance exit diameters and taper) of each factor at different levels was used as the measurement factor, and then the extreme difference value of these factors was calculated as the experimental investigation index of each factor at different levels.…”
Section: Data Processing Methodsmentioning
confidence: 99%
“…Related studies have shown that changes in important parameters such as the average power of the laser, overlap rate, and out-of-focus amount affect the quality of small holes when processing them with femtosecond lasers [16][17][18][19][20][21][22][23][24][25][26]. There are many factors that affect the quality of laser hole making during processing, and the test could not test all combinations of factors at the same time.…”
Section: Introductionmentioning
confidence: 99%
“…Laser drilling of micro-holes, with diameters below 200 μm is involved in various industrial manufacturing processes. In the pharmaceutical and biotech industries, there is a demand for micro-holes arranged in a grid pattern, as they are critical for fulfilling various functions such as injection or filtering [14,15]. The surface morphology surrounding these holes should be smooth [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous investigations have been conducted to explore the potential benefits of pulse shortening in order to reduce the ablation threshold and improve the quality of ablation [4,14]. Most of these studies have utilized femtosecond lasers operating in the near-IR range.…”
Section: Introductionmentioning
confidence: 99%
“…Hundreds of microholes (usually tens of microns in diameter) are generally distributed on the nozzle board of the inkjet print head [4]. The mainstream microhole machining methods mainly include mechanical processing [5], electrochemical machining [6,7], micro-EDM [8], and laser machining [9]. Yun et al [10] machined straight-wall microholes with a depth-to-diameter ratio of 1:1 on 100µm, 50µm, and 25µm thick copper and stainless steel plates, respectively.…”
Section: Introductionmentioning
confidence: 99%